Management dilemmas in pulmonary arterial hypertension associated with congenital heart disease. (August 2018) - Condliffe, R.; Clift, P.; Dimopoulos, K.; Tulloh, R.M.R.
There are few randomised controlled data to guide management of patients with pulmonary arterial hypertension associated with congenital heart disease (PAH-CHD). In this clinical review, common areas of uncertainty in the management of PAH-CHD are identified, the literature is summarised and discussed and a suggested approach offered for each clinical dilemma.